La céramique du groupe épiscopal d'Aradi/Sidi Jdidi (Tunisie) - Mukai, Tomoo 1970-; Capelli, Claudio (Roman and late antique Mediterranean pottery, 2016)
This study focuses on ceramic finds from the excavations (1996-2006) of the Episcopal Group of Sidi Jdidi, the ancient city of Aradi, in the hinterland of Hammamet in Tunisia